Praca jako wartość wobec problemu bezrobocia - Ślebarska, Katarzyna (Śląskie Studia Historyczno-Teologiczne, 2023)
The article is focused on a value of human work. In the case of increasing unemployment, especially unemployment of young people, the sense of the work is often depreciated. Unemployment of school-leavers is a specific situation, because they experience all consequences of unemployment before they get their first job. The consciousness the value of work is a main motivator in searching for a job. This topic is presented in the article.